2012
DOI: 10.1016/j.jaad.2011.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing infundibular crystalline folliculitis: A clinicopathological study

Abstract: NICF is both a distinct entity and an epiphenomenon in the context of other disorders. In regard to the common association with yeasts and gram-positive bacteria in the affected follicles, we hypothesize that NICF is pathogenetically linked to these organisms, which is supported by resolution of the lesions after topical or systemic antimycotic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 9 publications
0
35
0
Order By: Relevance
“…Lucke et al 1 initially reported it in 2 elderly men, describing it as transepidermal elimination of urate-like crystals. Another case, in a young woman with a history of acne vulgaris, was reported by Kossard et al 2 Recently a series of 12 cases was published by Denisjuk et al 3 NICF is clinically characterized by multiple, well-demarcated papules containing a central plug with a waxy appearance and a variably erythematous border. The lesions show a predilection for the face (especially the forehead), followed by the back and neck.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lucke et al 1 initially reported it in 2 elderly men, describing it as transepidermal elimination of urate-like crystals. Another case, in a young woman with a history of acne vulgaris, was reported by Kossard et al 2 Recently a series of 12 cases was published by Denisjuk et al 3 NICF is clinically characterized by multiple, well-demarcated papules containing a central plug with a waxy appearance and a variably erythematous border. The lesions show a predilection for the face (especially the forehead), followed by the back and neck.…”
Section: Discussionmentioning
confidence: 99%
“…The lesions show a predilection for the face (especially the forehead), followed by the back and neck. 3 Histologic findings show an epidermal depression filled with a plug containing birefringent filamentous material with a crystalline appearance enclosed by tiers of parakeratosis. The folliculocentric nature of the lesions may not be immediately apparent, sometimes requiring multiple serial sections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients present with waxy papules across the forehead or back. [1][2][3][4] We report the first case of NICF from North America. The plug is flanked by columns of parakeratin and seems to be of follicular origin in most instances.…”
Section: Introductionmentioning
confidence: 99%